CBMS-01 AGE-DEPENDENT GLIOBLASTOMA PROGRESSION SUPPRESSED BY NAD+. (16th December 2019) - Yamashita, Daisuke; Ozaki, Saya; Suehiro, Satoshi; Sonomura, Kazuhiro; Kondo, Toru; Sato, Taka-Aki; Kunieda, Takeharu; Nakano, Ichiro
Abstract: The rise in population aging worldwide is causing an unparalleled increase in death from many cancers, including glioblastoma (GBM). Here, we have explored the impact of aging and rejuvenation on GBM tumorigenesis. Compared with old GBM, young GBM displayed elevated neuronal/synaptic signaling via brain-derived neurotrophic factor (BDNF) and SLIT and NTRK like-family member 6 (SLITRK6), promoting favorable survival rates. These effects were attributed to the rise in nicotinamide adenine dinucleotide (NAD+) levels, as brain rejuvenation by parabiosis or administration of nicotinamide mononucleotide (NMN) in mice elicited a younger phenotype with activated neuronal/synaptic signaling and improved outcomes. Our data indicate that age-associated NAD+ loss contributes to the highly aggressive GBM in the elderly. These findings have therapeutic implications in GBM and provide mechanistic insights into the exacerbation of GBM tumorigenesis with age.